2022
DOI: 10.3390/nano12040598
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Drug-Loading Properties of Amphoteric Cassava Starch Nanoparticles

Abstract: Based on the characteristics of charge reversal around the isoelectric point (pI) of amphoteric starch-containing anionic and cationic groups, amphoteric cassava starch nanoparticles (CA-CANPs) are prepared by a W/O microemulsion crosslinking method using (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride as a cationic reagent and POCl3 as an anionic reagent, and the effects of preparation conditions on the particle size of the CA-CANPs are studied in detail in the present study. CA-CANPs with a smooth sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Xie et al prepared cassava starch nanoparticles via the microemulsion method, using POCl 3 as a crosslinking agent. In this work, the adsorption of the anticancer drug paclitaxel (PTX, C 47 H 51 NO 14 ) onto starch nanoparticles was studied, and the kinetics of the process were studied; 94.19% of free PTX was released from the dialysis bag in 0.9% saline (pH = 7) within 8 h. Compared with free PTX, the release rate of CA-CSNP-loaded PTX was 17.04% after 8 h and 37.61% after 96 h under the same conditions, showing the possibility of prolonging the therapeutic effect of the drug, which can improve the effectiveness of antitumor therapy [ 93 ]. All of this confirms the high prospects for the use of starch nanoparticles as drug carriers to provide a targeted effect on tumor cells.…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%
“…Xie et al prepared cassava starch nanoparticles via the microemulsion method, using POCl 3 as a crosslinking agent. In this work, the adsorption of the anticancer drug paclitaxel (PTX, C 47 H 51 NO 14 ) onto starch nanoparticles was studied, and the kinetics of the process were studied; 94.19% of free PTX was released from the dialysis bag in 0.9% saline (pH = 7) within 8 h. Compared with free PTX, the release rate of CA-CSNP-loaded PTX was 17.04% after 8 h and 37.61% after 96 h under the same conditions, showing the possibility of prolonging the therapeutic effect of the drug, which can improve the effectiveness of antitumor therapy [ 93 ]. All of this confirms the high prospects for the use of starch nanoparticles as drug carriers to provide a targeted effect on tumor cells.…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%
“…Entrapment effectiveness and in vitro release were used to assess the sustained release of medicines. Xie et al [ 113 ] reported that, due to the lower crystallinity of anionic and cationic groups, amphoteric cassava starch nanoparticles (CA-CANPs) encourage the drug to be loaded inside nanoparticles, improving the drug loading capacity and maintaining slow-release performance in a typical body fluid environment. Troncoso and Torres [ 114 ] clarified that, due to their hydrophobic characteristics, acetylated and hydroxypropylated starches are also among the most beneficial starches for drug-delivery applications ( Figure 7 ).…”
Section: Applications Of Starch Nano-particles (Snps)mentioning
confidence: 99%
“…This Special Issue of Nanomaterials, entitled “Nanostructure Design of Catalysts: Latest Advances and Prospects”, combines relevant research and review contributions that cover the latest nanocatalysts. This Special Issue covers thermal catalysis [ 5 , 6 , 7 , 8 ], photocatalysis [ 9 ], electrocatalysis [ 10 ], and adsorbent nanomaterials [ 11 , 12 , 13 ]. It contains six research papers on nanometer materials for catalysts, including for thermal catalysis, photocatalysis, electrocatalysis, and other fields, which provide some new ideas for the nanostructure design of catalysts.…”
mentioning
confidence: 99%
“…Finally, the study by Xie et al [ 12 ] used (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride as a cationic reagent. POCl 3 was used as an anionic reagent, which was prepared by the W/O microemulsion crosslinking method of amphoplastic cassava starch nanoparticles (CA-CANPs).…”
mentioning
confidence: 99%